Citrus biodiversity in Turkey - Tuzcu O. (Proceedings of the Mediterranean research network on certification of citrus (MNCC): 1998-2001, 2002)
General figures on citrus production, cultivated land and main growing species in Turkey are given. Citrus biodiversity evaluation in Turkey started with the establishment of 2 collection plots: Antalya Citrus Research Station (ATAE) and Tuzcu Citrus Collection (TCC). In the latter, composed of 865 genotypes (varieties and rootstocks) of different origin, a molecular characterization was also carried out as well as the assessment of the main diseases.
5. and 6. meeting of the CIHEAM Mediterranean Research Network on Certification of Citrus (MNCC), 2000/10/04-06, Algiers (Algeria) and 2001/10-11/26-01, Cairo (Egypt)